Efficient algorithms for optimal location queries in road network - Lim, Elson. (2013)
This report is base on a research paper Efficient Algorithms for Optimal Location Queries in Road Networks [1]. Given a Road Network, Data of Clients and Servers, the algorithm suggest areas on the edge where is optimize to set up a new Server.